The Paradoxical Agora The Social and the Political in between the People in the Marriage Corners of China - Pettier, Jean-Baptiste (Social Analysis, 2022)
Where is the political located? Since the early 2000s, the phe-nomenon of ‘marriage corners’ has mushroomed in city parks all over China. It consists of public gatherings attended by middle-to upper-middle-class parents attempting to find a partner for their child. The competitiveness of these gatherings and the vocabulary used by the participants when evaluating each other reflect political tensions of Chinese society without articulating them. Exploring this tension, the article argues for attending to the political ramifications of spaces where politics are silenced and denied. Hence, these marriage corners are examined as ‘paradoxical agoras’, that is, as constrained public spaces where politics are neither discussed nor decided, but rather embodied and practiced.
CRIS-Team Scopus Importer:2023-03-21
Keywords: China; market; marriage; ordinary politics; social competition